1994
DOI: 10.1093/eurheartj/15.suppl_d.98
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Receptor Subtypes and Cardiac Function

Abstract: KEY WORDS: AT, receptor subtype, AT 2 receptor subtype, human heart, heart failure. All the components of the renin-angiotensin system have been identified in the heart

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
16
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 43 publications
4
16
0
Order By: Relevance
“…Total Ang II receptor numbers in LV were in the range of 3.8 to 17.3 fmol/mg protein (Table), similar to the results reported by the previous studies, [13][14][15][16] but were lower than the receptor numbers (118, nϭ5) determined by de Gasparo et al 17,37,38 de Gasparo et al used combined fractions including plasma membranes and internalized receptors, whereas we and other studies [13][14][15][16] measured Ang II receptor numbers using only membrane fractions. In fact, Regitz-Zagrosek et al 14 found that the B max values determined with combined fractions were increased compared with those using only membranes.…”
Section: Discussionsupporting
confidence: 89%
“…Total Ang II receptor numbers in LV were in the range of 3.8 to 17.3 fmol/mg protein (Table), similar to the results reported by the previous studies, [13][14][15][16] but were lower than the receptor numbers (118, nϭ5) determined by de Gasparo et al 17,37,38 de Gasparo et al used combined fractions including plasma membranes and internalized receptors, whereas we and other studies [13][14][15][16] measured Ang II receptor numbers using only membrane fractions. In fact, Regitz-Zagrosek et al 14 found that the B max values determined with combined fractions were increased compared with those using only membranes.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is in accordance with the report that AT 1 ‐R predominates (AT 1 ‐R : AT 2 ‐R ≈ 80% : 20%) in myometrium during late ovine pregnancy although total Ang II binding decreases ∼90% as compared with that in non‐pregnant ewes where AT 2 ‐R is predominant (AT 1 ‐R : AT 2 ‐R ≈ 15% : 85%) (Cox et al 1993). Similar phenomena are also observed in human myometrium, which contains almost entirely AT 2 ‐R (AT 1 ‐R : AT 2 ‐R ≈ 1% : 99%) during non‐pregnancy, whereas during pregnancy AT 1 ‐R becomes predominant (AT 1 ‐R : AT 2 ‐R ≈ 66% : 34%) (de Gasparo et al 1994; Bing et al 1996). This alteration in distribution of Ang II subtype receptors in human myometrium appears to be due to down‐regulation of AT 2 ‐R expression with no changes in AT 1 ‐R density (de Gasparo et al 1994; Bing et al 1996).…”
Section: Expression Of Ang II Receptors Enos and Inducible Nos (Inossupporting
confidence: 76%
“…Similar phenomena are also observed in human myometrium, which contains almost entirely AT 2 ‐R (AT 1 ‐R : AT 2 ‐R ≈ 1% : 99%) during non‐pregnancy, whereas during pregnancy AT 1 ‐R becomes predominant (AT 1 ‐R : AT 2 ‐R ≈ 66% : 34%) (de Gasparo et al 1994; Bing et al 1996). This alteration in distribution of Ang II subtype receptors in human myometrium appears to be due to down‐regulation of AT 2 ‐R expression with no changes in AT 1 ‐R density (de Gasparo et al 1994; Bing et al 1996).…”
Section: Expression Of Ang II Receptors Enos and Inducible Nos (Inossupporting
confidence: 76%
“…Despite low AT 2 receptor expression in adult tissues, their abundance is increased after blood vessel injury 2 and can equal or exceed that of AT 1 in pathophysiological conditions. 3 The functional significance of AT 2 receptors remains uncertain. However, a recent study demonstrated that intrabrachial infusion of the AT 2 receptor antagonist PD123319 had significant systemic effects on mean arterial pressure during placebo and therapy with the AT 1 receptor antagonist telmisartan without affecting forearm blood flow, suggesting the presence of functionally effective AT 2 receptors.…”
mentioning
confidence: 99%